Comparing needle types and aspiration techniques in EUS-TA to optimize diagnostic efficacy and specimen quality in patients with pancreatic lesions - Rumin Shang; Xiangming Han; Fangwei He; Lihua Huang; Cui Zeng; Kun Chen; Fei Lv; Xiangwu Ding (Frontiers in Medicine)
PurposeIn solid pancreatic lesions (SPLs), we compared the diagnostic efficacy of a 19G fine-needle aspiration (FNA) needle and a 22G ProCore fine-needle biopsy (FNB) needle, We also compared the specimen quality between the standard suction (SS) technique and heparinized wet-suction (HWS) technique.MethodsAll cases of endoscopic ultrasound-guided tissue acquisition (EUS-TA) by 19G FNA or 22G FNB for SPLs in a single-centre hospital were retrospectively reviewed. The diagnostic yield was compared between the 19G and 22G groups. Univariate and multivariate logistic regression analyses were used to identify optimal factors for a correct histological diagnosis. We also examined tissue integrity, the length of the tissue cores, and the rate of blood cell contamination between the SS and HWS groups.ResultsOne hundred seventy-one and sixty-three patients were included in the comparisons of needle types and suction techniques, respectively. The 19G group had higher histological diagnosis rates compared to the 22G group for the first pass (87.8% vs. 70.4%, p = 0.005), the second pass (82.2% vs. 65.4%, p = 0.012), the first two passes (90.0% vs. 72.8%, p = 0.004), and the final diagnosis (91.1% vs. 79%, p = 0.025). Through macroscopic on-site evaluation, a significantly higher proportion of patients in the 22G group required a third needle pass compared to the 19G group (88.9% vs. 67.8%, p = 0.002). The total procedure time was shorter in the 19G group than in the 22G group (p < 0.001). The HWS group showed superiority over the SS group in terms of the total length of tissue cores (p < 0.001) and the total length of white tissue cores (p = 0.005). The HWS group, compared to the SS group, can enhance the tissue integrity (p = 0.024) and reduce blood cell contamination (p = 0.040) during the first needle pass. There was no significant difference in complication rates between the needle puncture groups (p = 0.770) or the aspiration technique groups (p = 0.654).ConclusionCompared to the 22G FNB needle, endoscopists should consider using the 19G FNA needle when appropriate. Furthermore, the use of the HWS technique for the first pass is recommended to improve specimen quality.